A review of Cordylus machadoi (Squamata: Cordylidae) in southwestern Angola, with the description of a new species from the Pro-Namib desert - Stanley, Edward L.; Ceríaco, Luis M. P.; Bandeira, Suzana; Valerio, Hilaria; Bates, Michael F.; Branch, William R. (Zootaxa, 2016)
The girdled lizard genus Cordylus is represented in Angola by two species, Cordylus angolensis and C. machadoi, separated from their nearest congeners by over 700 km. Here we describe a new species, Cordylus namakuiyus sp. nov., endemic to the arid lowlands west of the southern Angolan escarpment. Phylogenetic analysis using three mitochondrial and eight nuclear genes shows that the low-elevation forms and the proximate, high-elevation species C. machadoi are genetically divergent and reciprocally monophyletic, and together form the earliest diverging lineage of the northern Cordylus clade. Morphological data, collected using computed tomography and traditional techniques (scalation and morphology), identify consistent phenotypic differences between these high- and low-elevation species and allows for a detailed description of the osteology and osteodermal arrangements of the new species. A series of 50 specimens, collected during the 1925 Vernay expedition to southwestern Angola and housed at the American Museum of Natural History, are assigned to the new species, although the identity of Cordylus from northern Namibia remains ambiguous and requires further investigation.